Differential symbiotic compatibilities between rhizobium strains and cultivated and wild soybeans revealed by anatomical and transcriptome analyses - Zadegan, Sobhan Bahrami; Kim, Wonseok; Abbas, Hafiz Muhammad Khalid; Kim, Sunhyung; Krishnan, Hari B.; Hewezi, Tarek (Frontiers in Plant Science, 2024)
Various species of rhizobium establish compatible symbiotic relationships with soybean (Glycine max) leading to the formation of nitrogen-fixing nodules in roots. The formation of functional nodules is mediated through complex developmental and transcriptional reprogramming that involves the activity of thousands of plant genes. However, host transcriptome that differentiate between functional or non-functional nodules remain largely unexplored. In this study, we investigated differential compatibilities between rhizobium strains (Bradyrhizobium diazoefficiens USDA110 Bradyrhizobium sp. strain LVM105) and cultivated and wild soybeans. The nodulation assays revealed that both USDA110 and LVM105 strains effectively nodulate G. soja but only USDA110 can form symbiotic relationships with Williams 82. LVM105 formed pseudonodules on Williams 82 that consist of a central nodule-like mass that are devoid of any rhizobia. RNAseq data revealed that USDA110 and LVM105 induce distinct transcriptome programing in functional mature nodules formed on G. soja roots, where genes involved in nucleosome assembly, DNA replication, regulation of cell cycle, and defense responses play key roles. Transcriptome comparison also suggested that activation of genes associated with cell wall biogenesis and organization and defense responses together with downregulation of genes involved in the biosynthesis of isoprenoids and antioxidant stress are associated with the formation of nonfunctional nodules on Williams 82 roots. Moreover, our analysis implies that increased activity of genes involved oxygen binding, amino acid transport, and nitrate transport differentiates between fully-developed nodules in cultivated versus wild soybeans.